2018
DOI: 10.1080/10409238.2018.1488804
|View full text |Cite
|
Sign up to set email alerts
|

The molecular era of protein S-acylation: spotlight on structure, mechanisms, and dynamics

Abstract: S-Acylation (commonly referred to as S-palmitoylation) is a post-translational modification consisting in the covalent attachment of an acyl chain to a cysteine residue of the target protein. The lability of the resulting thioester bond gives S-acylation an essential characteristic: its reversibility. S-acylation dynamically regulates different aspects in the life of a protein (including stability, localization, interactome, and function) and, thus, plays critical roles in cellular physiology. For long, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
129
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 299 publications
(410 reference statements)
3
129
0
Order By: Relevance
“…So far, many global S-acylproteomic studies were performed using ABE and its derived methods, which are independent of metabolic labeling and have the potential of capturing the entire S-acylproteome in any biological samples including tissues and extracellular vesicles in biofluids. 5,26 In theory, ABE methods are able to capture more S-acylated proteins than other methods such as MLCC, which is biased towards the enrichment of S-acylated proteins with rapid turnover. 5 Nevertheless, an analysis of S-acylated proteins compiled in the SwissPalm (v2) 3 -a comprehensive database of Sacylated proteins identified since 1981-revealed that only 41% (1,173 out of 2,881) of the human S-acylproteome and 33% (976 out of 2,939) of the mouse S-acylproteome were discovered by ABE studies ( Fig.…”
Section: Results and Discussion Current Abe Methods Suffer From High mentioning
confidence: 99%
“…So far, many global S-acylproteomic studies were performed using ABE and its derived methods, which are independent of metabolic labeling and have the potential of capturing the entire S-acylproteome in any biological samples including tissues and extracellular vesicles in biofluids. 5,26 In theory, ABE methods are able to capture more S-acylated proteins than other methods such as MLCC, which is biased towards the enrichment of S-acylated proteins with rapid turnover. 5 Nevertheless, an analysis of S-acylated proteins compiled in the SwissPalm (v2) 3 -a comprehensive database of Sacylated proteins identified since 1981-revealed that only 41% (1,173 out of 2,881) of the human S-acylproteome and 33% (976 out of 2,939) of the mouse S-acylproteome were discovered by ABE studies ( Fig.…”
Section: Results and Discussion Current Abe Methods Suffer From High mentioning
confidence: 99%
“…Functional enrichment analysis identified a series of cell functions overrepresented in EVs in comparison to M. More specifically, the palmitoylproteins significantly enriched in both L-and S-EVs were involved in pyridine nucleotide metabolism and cell adhesion ( Figure 3B and Suppl. Table 2), including proteins known to be involved in modulating cell polarity, adhesion and migration 46 . These comprised membrane-anchored integrins (ITGA2, ITGA6, ATGB4), claudins (CLDN1, CLDN1), and cytoskeletal proteins such as the Rho-associated moesin (MSN), vinculin (VCL), ezrin (EZR), ROCK2 and the Ras GTPase-activating-like protein IQGAP1 (Suppl.…”
Section: L-and S-evs Exhibit Distinct Profiles That Distinguish Them mentioning
confidence: 99%
“…Enzymes that acylate HA (or any other viral glycoprotein) have not been identified, but cellular proteins are acylated by members of the ZDHHC family of proteins [27][28][29][30]. ZDHHC proteins are polytopic membrane proteins containing an Asp-His-His-Cys (DHHC) motif as the catalytic centre in one of their cytoplasmic domains.…”
Section: Introductionmentioning
confidence: 99%